The pituitary tumour‐transforming gene 1/delta‐like homologue 1 pathway plays a key role in liver fibrogenesis. (30th January 2022) - Perramón, Meritxell; Carvajal, Silvia; Reichenbach, Vedrana; Fernández‐Varo, Guillermo; Boix, Loreto; Macias‐Muñoz, Laura; Melgar‐Lesmes, Pedro; Bruix, Jordi; Melmed, Shlomo; Lamas, Santiago; Jiménez, Wladimiro
Abstract: Background and Aims: PTTG1 is almost undetectable in adult livers but is highly expressed in hepatocarcinoma. While little is known about its involvement in liver fibrosis, PTTG1 expression is associated with DLK1 . We assessed the role of the PTTG1/DLK1 pathway in fibrosis progression and the potential therapeutic effect of PTTG1 silencing in fibrosis. Methods: Pttg1 and Dlk1 were studied in liver and isolated cell populations of control and fibrotic rats and in human liver biopsies. The fibrotic molecular signature was analysed in Pttg1 −/− and Pttg1 +/+ fibrotic mice. Finally, Pttg1 silencing was evaluated in rats as a novel antifibrotic therapy. Results: Pttg1 and Dlk1 mRNA selectively increased in fibrotic rats paralleling fibrosis progression. Serum DLK1 concentrations correlated with hepatic collagen content and systemic and portal haemodynamics. Human cirrhotic livers showed greater PTTG1 and DLK1 transcript abundance than non‐cirrhotic, and reduced collagen was observed in Pttg1 Pttg1 −/− mice. The liver fibrotic molecular signature revealed lower expression of genes related to extracellular matrix remodelling including Mmp 8 and 9 and Timp4 and greater eotaxin and Mmp13 than fibrotic Pttg1 +/+ mice. Finally, interfering Pttg1 resulted in reduced liver fibrotic area, lower α‐Sma and decreased portal pressure than fibrotic animals. Furthermore, Pttg1 silencing decreased the transcription of Dlk1, collagens I and III, Pdgfrβ, Tgfrβ, Timp1, Timp2 and Mmp2 . Conclusions: Pttg1 / Dlk1 are selectively overexpressed in the cirrhotic liver and participate in ECM turnover regulation. Pttg1 disruption decreases Dlk1 transcription and attenuates collagen deposition. PTTG1/DLK1 signalling is a novel pathway for targeting the progression of liver fibrosis.